Gastric outlet obstruction by a polypoid tumor: Author’s reply - Suna, Nurettin; Öcal, Serkan; Özer Etik, Diğdem; Boyacıoğlu, Seda (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Suna N, Serkan Ö, Özer Etik D, Boyacıoğlu S. Gastric outlet obstruction by polypoid tumor: Author’s Reply. Turk J Gastroenterol 2018; 29: 243-4.